2015
DOI: 10.5433/1679-0359.2015v36n1p443
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade econômica do uso da glicerina bruta em dietas para cordeiros terminados em confinamento

Abstract: O objetivo foi avaliar a viabilidade econômica de níveis crescentes de glicerina bruta (GB) em dietas para cordeiros na fase de terminação em confinamento. O experimento foi desenvolvido na Universidade Estadual do Sudoeste da Bahia, Itapetinga-BA. Foram utilizados 25 cordeiros mestiços Santa Inês x Dorper, machos castrados, com 24 ± 2,0 kg, alojados em baias individuais. O delineamento utilizado foi inteiramente casualizado, com cinco tratamentos e cinco repetições. Os tratamentos consistiram de níveis cresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…In this activity, confinement is being considered as a viable alternative by allowing an intensification of animal production that is associated with reduced time to produce housing in term of the quantity and quality required by the market and accelerated returns on the capital employed (BARROS et al, 2015;REGO et al, 2015). In this production system, the fact is that conventional food concentrates, such as corn and soybean meal, are crucial for the rise in costs of confinement (XENOFONTE et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this activity, confinement is being considered as a viable alternative by allowing an intensification of animal production that is associated with reduced time to produce housing in term of the quantity and quality required by the market and accelerated returns on the capital employed (BARROS et al, 2015;REGO et al, 2015). In this production system, the fact is that conventional food concentrates, such as corn and soybean meal, are crucial for the rise in costs of confinement (XENOFONTE et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Food changeover was higher for the confined group with 21% crude glycerin, although its major consumption for weight gain means did not affect the final gross margin (R$34.01 per animal) in this diet (Table 6). Barros et al (2015) also found positive results from the inclusion of glycerin in animals' diet (0, 2.65, 5.33, 8.06 and 10.84%) when they checked the economic feasibility of using it in confined lamb feed. However, these animals did not present satisfying performances, they had less salable meat.…”
Section: Resultsmentioning
confidence: 93%
“…Factors such as the chemical composition of NDF (lignin type and content and their physical-chemical interaction with the other components), dimension of potentially degradable (NDFpd) and undegradable (NDFi) fractions, initial size, density, and fragility of particles, as well as the ruminal microbial activity should be considered as directly affecting the parameters of degradation and transit dynamics through the digestive tract, which modulate the effects of NDF on the consumption and digestion of nutrients (Lund et al 2007). Barros et al (2015), Lage et al (2014), andGunn et al (2010) found negative linear responses over the DM intake in lambs, evaluating CG inclusions of up to 10.84, 12, and 20 % of the diet, respectively. Moreover, Souza et al (2015) reported increases in DM, EE, and NDFap intake with the inclusion of 60 g CG/kg DM in the diet of lambs in confinement.…”
Section: Discussionmentioning
confidence: 99%